Effectiveness of Dry Lab Based Augmented Reality to Overcome the Misconceptions of Students on Solar System and Eclipse Learning Topics - Hamdi Akhsan; Muhammad Yusup; Melly Ariska; Tsabita Husna; Dwita Kartika Sari (Postgraduate, University of Mataram, 2023)
In science learning there are many important concepts that must be understood. The solar system is a complex and abstract material because it cannot be seen directly by human senses resulting in students experiencing misconceptions.Â Interactive learning media is needed to help students understand concepts. One of the learning media that can be applied is augmented reality based on dry lab simulation. This study aims to determine the effectiveness of using Dry Lab simulation to overcome misconceptions of earth and solar system material in junior high school. This research uses experimental research methods with Pre-experimental research models. The overall research results, the average effectiveness was 45.16%, which showed less effective results. Partially for the two sub-concepts of planets and solar and lunar eclipses, the average effectiveness is 65.5%, which shows that the dry lab simulation is effective in changing students' misconceptions